Analysis of the Influence of Green Altruism and Green Perceived Value on Purchase Intention for a Green Beauty Brand in Jabodetabek - Munandar, Jono Mintarto; Azzahra, Kamilla; Maulida, Annisaturrahmah (The South East Asian Journal of Management, 2025)
Research Aims: To analyse the effect of green altruism and green perceived value on the purchase intention of AVOSKIN skincare products in Jabodetabek. Design/Methodology/Approach: The data used consisted of primary data in the form of questionnaires and secondary data in the form of literature reviews. The number of respondents in this study was 228, using non-probability sampling techniques and purposive sampling methods. The data analysis method used in this study included descriptive analysis to identify consumer characteristics and SEM-PLS analysis through a second-order construct with the embedded two-stage approach. Research Findings: Green perceived value has a significant and positive effect on purchase intention, while green altruism does not have a significant effect. Green attitude can mediate the effect of green altruism and green perceived value on purchase intention. Theoretical Contribution/Originality: This study examines green altruism and green perceived value in driving purchase intention, with AVOSKIN as a case study. The findings provide insights applicable to green beauty brands in Southeast Asia. Managerial Implication in the Southeast Asian Context: Green beauty brands can enhance purchase intention through UGC, IMC, and sustainability programs such as recycling and eco-tourism, fostering loyalty and sustainable behaviour. Research Limitation & Implications: This study is limited to AVOSKIN and Jabodetabek consumers. Future research should cover more brands and regions in Southeast Asia.